Food loss and waste reduction strategies to fill the protein gap - Xuezhen, Guo (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In this study, Wageningen University and Research (WUR) investigated the FLW reduction strategies both from the prevention and valorization perspectives. Firstly, we looked into the protein potentials of using the FLW to directly fill the protein gaps at the country level. If all the FLW of a country are avoided, to what extent the protein gap of that country could be closed. Then, we investigated the alternative scenario of feeding all the FLW to chickens to see if the converted chicken proteins can fill the protein gap in that country.